Validation of a New Cognitive Screening Method for Stroke Patients - Katri Saar; Hannu Nyrkkö; Asko Tolvanen; Pekka Kuikka; Erja Poutiainen; Tuija Aro (Behavioural Neurology)
Objective. Two million adults under fifty years of age have a cerebral stroke every year worldwide. Neuropsychological assessment is the best way to identify poststroke cognitive dysfunction, but it is often time-consuming and can be tiring for the patient, and hospitals vary in their availability of neuropsychological expertise. A valid and reliable cognitive screening method could be advantageous in identifying patients who need comprehensive neuropsychological examination. Our purpose in this study was to validate a newly developed cognitive screening method as an identifier of cognitive dysfunction after stroke in working-aged patients. Methods. We analyzed new cognitive screening method concurrent validity by comparing it in two groups formed on the basis of a comprehensive neuropsychological examination for 77 stroke patients. We identified the best balance of sensitivity and specificity by using receiver operating characteristic curve analysis and investigated the impact of the sociodemographic variables to the screening method total score variation. Results. We found a significant correlation between the method’s total score and performance in neuropsychological examination. The cognitive method’s internal consistency was strong; Cronbach’s alpha for all items was .818. The best balance of sensitivity (88%) and specificity (50%) was found at a total score cut point of 138. Subjects’ age and length of education were each responsible for 10% of total score variation. Conclusions. This study shows promising results for this new cognitive screening tool’s ability to identify poststroke cognitive decline and patients’ need for further detailed neuropsychological examination.